2022
DOI: 10.1371/journal.pone.0263471
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among hospitalized COVID-19 patients and risk score formulation for prioritizing tertiary care—An experience from South India

Abstract: Background We retrospectively data-mined the case records of Reverse Transcription Polymerase Chain Reaction (RT-PCR) confirmed COVID-19 patients hospitalized to a tertiary care centre to derive mortality predictors and formulate a risk score, for prioritizing admission. Methods and findings Data on clinical manifestations, comorbidities, vital signs, and basic lab investigations collected as part of routine medical management at admission to a COVID-19 tertiary care centre in Chengalpattu, South India betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
29
1
Order By: Relevance
“…In addition, a lower Sa/FiO 2 ratio and a decreased lymphocyte count were associated with death by COVID-19 ( Henry et al., 2020 ; Huang and Pranata, 2020 ; Booth et al., 2021 ; Pons et al., 2021 ; Gopalan et al., 2022 ; Soto et al., 2022 ). It should be noted that lymphopenia might occur due to consequent apoptosis of activated CD4+T cells by SARS-CoV-2 ( Shen et al., 2022 ), thereby inducing immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a lower Sa/FiO 2 ratio and a decreased lymphocyte count were associated with death by COVID-19 ( Henry et al., 2020 ; Huang and Pranata, 2020 ; Booth et al., 2021 ; Pons et al., 2021 ; Gopalan et al., 2022 ; Soto et al., 2022 ). It should be noted that lymphopenia might occur due to consequent apoptosis of activated CD4+T cells by SARS-CoV-2 ( Shen et al., 2022 ), thereby inducing immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated NLR has been used successfully as an independent prognostic parameter of bacterial infections treatment outcome [34,55], hypertension, heart failure or progression of cancer and response to drug therapy [56]. Endothelial cell death following cellular damage caused by viral infection may be indicated by elevated levels of NLR due to various inflammatory cells, including neutrophils, which in turn leads to multisystemic inflammation by secreting large quantities of cytokines [46,57].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, compared to the prognosis of COVID-19 severity with scoring systems, the prediction utility of the published models of prognosis based strictly on laboratory parameters is not limited by the clinical data which might be unavailable for nonsevere patients at admission [82]. Moreover, such models could be more appropriate for prediction of all clinical outcomes considering that multiple-organ damage is more pronounced in nonsurvivors and the individual relevance of the components of risk scores in the prediction of mortality, such as the levels of SaO2 at admission [57,82].…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 Yet; several studies suggested that rather than a single parameter, multiple markers should be used as predictors of severity and mortality in patients with COVID-19. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…45,46 Yet; several studies suggested that rather than a single parameter, multiple markers should be used as predictors of severity and mortality in patients with COVID-19. 47,48 Regardless of all the above findings, the incomplete knowledge of the association between COVID and ACE2 has led to debates concerning the use of RAAS inhibitors. Our study found no concern regarding the inflammatory markers; we even found a better ratio of IL-6/IL-10 in patients treated with RAAS inhibitors.…”
mentioning
confidence: 99%